Interrelations between changes in parameters of HRV, EEG and humoral immunity at patients with chronic pyelonephritis and cholecystitis - Kul’chyns’kyi, Andriy B; Zukow, Walery; Korolyshyn, Tetyana A; Popovych, Igor L (Journal of Education, Health and Sport, 2017)
<pre style="text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Background. The immunological homunculus conception considers somatotopic organization to СNS regulation of immune system. Previously, we have shown within the immunological homunculus conceptionthat take place causal relationships parametersofEEG and HRV, on the one hand, and the parameters of cellular and humoral immunity as well as phagocytose, on the other hand. The purpose of this study is to find out the relationships between induced by balneotherapy changesin parametersofEEG and HRV, on the one hand, and the parameters of immunity, on the other hand. Methods. Inbasalconditionsin33 menand 10 womenwithchronicpyelonephritisandcholecystitisinremission, werecordedtwice, before and after balneotherapy at the spa Truskavets’, EEG (“NeuroCom Standard”)andHRV (“Cardiolab+VSR”). In blood estimated routine parameters of HumoralImmunity on a set of I and II levels recommended by the WHO. Results. We detected that changes in relative level CD22+ B-Lymphocytes upregulated by parasympathetic outflows and β-rhythm generating structures that are projected onto the loci O2, Fp1, F3 and F4, while downregulated by sympathetic outflows and θ-rhythm generating structures that are projected onto the locus T5. Serum level of IgA upregulated by parasympathetic outflows and α-rhythm generating structures that are projected onto the loci T3 and C3 as well as δ-rhythm generating structures onto F7 and T5, while downregulated by sympathetic outflows and θ-rhythm generating structures that are projected onto the loci T5, F7, Fp2, F3, F8 and F4. Serum level of CIC upregulated by parasympathetic outflows and α-rhythm generating structures that are projected onto the loci T4, Fp2, T3, F8 and C3 as well as θ-rhythm generating structures onto the loci T3 and T6, while downregulated by sympathetic outflows and β-rhythm generating structures that are projected onto the loci Fp1, F3 and P4 as well as δ-rhythm generating structures onto T4.Unlike the previous parameters serum level of IgM downregulated by parasympathetic outflows and α-rhythm generating structures that are projected onto the loci T3 and T6 as well as β-rhythm generating structures onto the locus T5, while upregulated by sympathetic outflows and θ-rhythm generating structures that are projected onto the loci F3, Fp2, T5, F4, O1 and F8. Serum level of IgG downregulated by parasympathetic outflows, while upregulated by sympathetic outflows and δ-rhythm generating structures that are projected onto the loci O2 and F8 as well as α-rhythm generating structures onto C3. Conclusion. The results are supplemented and refined Tracey’s immunological homunculus conception.